Application Of Internet Of Things On Temperature Measuring System On Wafer Furnace Sintering Process - Abd Aziz, Muhamad Syaiful Akmal (Universiti Sains Malaysia, 2018)
Internet-of-Things (loT) is a system that broadens the internet services in today life. Applications of loT are widening and are expected to widen more in the future as this sector has been identified one of the critical sector that need to be nurtured even by Malaysian government. Uses of new technologies in IoT environment are increasing rapidly even in our country. The implementation of IoT to furnace temperature measuring system has helped the process of using the furnace or heater to be more efficient. This is because even when no one is around the heater during it is operating we can control the on or off of the furnace by using only mobile phone to send instruction to the cloud server and the cloud server will communicate with the Arduino board to relay or turn off the heater and vice versa. This will enable us to avoid any unnecessary damage of overheating of the heating. Implementation of IoT to the system also will help us to monitor online temperature of the heater without delayed and hence help to make the wafer sintering process becomes much better .The IoT system without doubt will help save the electricity and therefore make the consumption of power for the heater comes more efficient.